Entre el rito y la rutina: el rol de cuidadora en las mujeres de Medellín (2001)
ABSTRACT: Qualitative investigation carried out between July of 1997 and September of 1999 in the city of Medellin that, through in depth interviews following a substantiated theory, seeks to gain an insight into the way women from Medellin perceive assume and live, today, the fact of being the main suppliers of care in the family, and to analyze the implications of this role their integral development as persons. The study points to care as a bio-psychosocial category that transcends the maintenance of a biological life. It can be observed that women conceive their full development as a result of the simultaneous execution of their role as caregiver and worker, which makes them carry out a harmonious work that implies transformations and conflicts in family dynamics. The logic of care practices in feminine daily life is revealed and the place occupied by them in cultural attitudes toward care in gender and mental health relationships are identified.